(untitled) (Journal of Parents and Teachers, 2012)
The today’s increasing distance from spirituality is a fact that we have to consider in school. The use of spiritual cinema as a way of contemplation develops some aspects of spiritual intelligence such as the desire of transcendental things and the personal search for God. The biggest challenge we can have as teachers, is to carry out more and more creative activities in classroom to increase the students’ spiritual horizon.